2012
DOI: 10.1136/injuryprev-2012-040467
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the association between the amount of exposure and the frequency of self-reported involvement in a road crash

Abstract: We tried to obtain preliminary evidence to test the hypothesis that the association between driving exposure and the frequency of reporting a road crash can be decomposed into two paths: direct and indirect (mediated by risky driving patterns). In a cross-sectional study carried out between 2007 and 2010, a sample of 1114 car drivers who were students at the University of Granada completed a questionnaire with items about driving exposure during the previous year, risk-related driving circumstances and involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There is evidence that both more experience and older age may be important factors mitigating crash risk. 30,31 Our study showed that in OSA patients a greater level of prior driving experience was associated with better driving simulator performance. However, prior driving experience effects are likely to also apply to non-OSA drivers.…”
Section: Discussionmentioning
confidence: 67%
“…There is evidence that both more experience and older age may be important factors mitigating crash risk. 30,31 Our study showed that in OSA patients a greater level of prior driving experience was associated with better driving simulator performance. However, prior driving experience effects are likely to also apply to non-OSA drivers.…”
Section: Discussionmentioning
confidence: 67%
“…Also, participants of events were targeted (e.g., bicycle event) for a limited study region (see, e.g., [50,136]). To represent young drivers, most of the studies targeted high school students, university students and driving license learners (see, e.g., [28,55,79,137]). A random recruitment of citizens was usually used to collect the data representative for an entire nation, for example, in Goldenbeld et al [22].…”
Section: Discussionmentioning
confidence: 99%
“…Again, Martínez-Ruiz et al (2015) reported that risk exposure contributed to increases in fatality rates after estimating the mortality rate ratios for different age categories and gender. Jiménez-Mejías et al (2013) collected data on prior driving exposure (measured a year before measuring the road traffic crashes), risk-related factors and road traffic crashes among a sample of 1114 car drivers in a cross-sectional survey. They reported that prior risk exposure is related to risk of road traffic crash and that this relationship is also mediated by risky driving .…”
Section: Risk Exposure and Road Traffic Crashesmentioning
confidence: 99%